Interview with Dr. Iván Bélyácz - Csapi, Vivien (Public Finance Quarterly, 2024)
It seems like yesterday, but it will soon be five years since Professor Iván Bélyácz, full member of the Hungarian Academy of Sciences and head of the Doctoral School of the Faculty of Economics of the University of Pécs, retired. I could say that he started his well-deserved retirement, but looking at the MTMT profile, the list of PhD students who have reached the top under his mentorship, the honorary professorship of the Partium University of Oradea, or the 2022 Széchenyi Prize, it has been a productive five years. He continues to be a key figure in the Hungarian scientific community, a mentor and advisor to many of us. We also need his experience and guidance in the accelerated, digitalised world around us, which at the same time struggles with its sustainability.